Overcoming challenges in managing public schools of novice principals - Leon, Jayson Ryan T. De; Lim, Rich Paulo S.; Embalsado, Justin Vianey M.; Madlambayan, Jed V.; Credo, Chillet G.; Salunga, Ricardo C. (International Journal of Evaluation and Research in Education (IJERE), 2025)
A qualitative phenomenological approach was utilized in this study to explore the challenges experienced by novice school principals and how they overcome these challenges in managing their schools in the Division of Mabalacat City during school year 2023-2024. Guided by in-depth one-on-one semi-structured interviews, data was gathered from nine public elementary school principals. With the transcribed data, coding was employed using thematic analysis. Results showed that novice principals’ challenges are categorized into two: i) interpersonal challenges, including keeping the school safe and conducive and engaging with stakeholders, and ii) intrapersonal challenges, which include transitioning to higher roles and responsibilities and catching up with the new knowledge and skills needed to acquire. Moreover, novice principals experienced in overcoming these challenges were also examined. Findings revealed that growing interpersonal skills by establishing a good relationship with stakeholders and building rapport with teachers and growing intrapersonal skills by never stopping learning and having the right attitude would help them cope with their difficulties in managing the school. Finally, a proposed novice principals’ challenges model framework was developed and recommended for use in the Division of Mabalacat City to improve the knowledge, skills, and qualities of beginning and aspiring principals with their new roles in managing their schools.